Navigating The Challenges Of Globalization (The Socio-economic Dynamics Of Salt Farmers) - Mustofa, Mustofa; Diartho, Herman Cahyo; Zainuri, Zainuri; Luthfi, Agus (UNIVERSITAS PAKUAN, 2025)
This study examines the socio-economic dynamics of salt farmers in the northern coast of Probolinggo Regency under the pressures of globalization. Farmers face structural vulnerabilities such as weak bargaining power, dependence on middlemen, and limited access to technology and markets, raising questions about how they sustain livelihoods while maintaining cultural identity. The novelty lies in integrating economic ethnography with cultural theme analysis, showing that economic practices are deeply embedded in cultural frameworks. An economic ethnography approach was applied through participatory observation, in-depth interviews, and documentation, supported by qualitative analysis with ATLAS.ti. Snowball sampling involved fifty farmers with diverse age, experience, land ownership, and production orientation. The findings reveal five main domains: production strategies, distribution and marketing, socio-cultural values, institutional relations, and attitudes toward technology. Taxonomic analysis grouped these into survival, social values, and global adaptation, while componential analysis highlighted six contrasting dimensions. Cultural theme analysis emphasized two guiding principles blessings and heritage. Modernization and sustainability of salt agribusiness require aligning innovation and policy with local cultural values to ensure inclusivity and resilience.